Permanent Downhole Seismic Monitoring For Co2 Geosequestration: Stage 3 of the Co2crc Otway Project - Pevzner, Roman; Glubokovskikh, Stanislav; Tertyshnikov, Konstantin; Yavuz, Sinem; Egorov, A.; Sidenko, E.; Popik, Sofya; Ricard, L.; Correa, J.; Wood, T.; others (2019)
Time lapse (TL) seismic plays a key role in monitoring of changes in the subsurface caused by reservoir production or C02 geosequestration However, applicability of the TL seismic is limited by several factors, which include: relatively high cost; relatively high degree of invasiveness and associated land access issues; sparseness in time and usually significant delay between the acquisition and availability of the interprétable data. Stage 3 of the CO2CRC Otway project is aiming to address these issues through deployment of a permanent seismic monitoring system built on a combination of permanent orbital vibrators and multiple closely spaced wells instrumented with fibre optic cables for distributed acoustic sensing. Here we discuss the seismic monitoring program for Stage 3 and illustrate it with the results of a number of trials conducted on site while developing the program.